Synthesis of Nanomaterials, Nanofertilizers and Research of their Impact on Agricultural Plants - Javadov, N.H.; Aliyev, B.H.; Kazimov, N.F.; Galandarov, G.A. (Herald of Azerbaijan Engineering Academy, 2021)
The article discusses the latest scientific innovations in the field of synthesis of nanomaterials, nanofertilizers and their impact on agricultural crops, and also compares the results with the work carried out in this area. It was shown that a nanomaterial - a nanotube with high quality and high structural parameters was synthesized from the gas phase by chemical deposition in the laboratory. The positive effect of the obtained nanotubes on the development of "Gobustan" soft wheat variety was studied and the reasons for the development trend were analyzed. A device has been developed for the production of magnesite nanoparticles (Fe2O4), which are used as nanofertilizers in agriculture, increase the productivity of plants, increase the amount of chlorophyll and carbohydrates in plants and are used in various fields of science. The second part of the article examines the effect of nanoparticles on the development of plants (wheat). It was found that nanoparticles of silicon and silicon oxide in a certain concentration affect the pores of the root system of a plant, promote plant growth, and have a positive effect on its productivity. The obtained results confirm the vitality of use of nanomaterials in agriculture and make the use of such materials important for the future development of the agricultural sector.